Questions kids ask about earth and sky - Comely, Richard; Dickie, Alison (Grolier Toronto, 1988)
Questions Kids Ask About Earth and Sky answers children's inquiries about the natural world, exploring topics like weather, the atmosphere, and celestial bodies to spark curiosity and scientific wonder.